Efisiensi Penanganan Perkara Perdata melalui Implementasi Sistem E-Court di Indonesia - Delfina, Dinda (Jurnal Administrasi Politik dan Sosial, 2025)
This study aims to analyze the efficiency of civil case handling through the implementation of the e-Court system in Indonesia, which was introduced under Supreme Court Regulation No. 1 of 2019. The research background stems from the need for judicial reform to achieve a simpler, faster, and more cost-effective process, as well as a response to the growing demand for digitalization in public services. The research method employed is normative juridical with a statutory and case approach, supported by secondary data such as regulations, court decisions, and academic articles published between 2020–2025. The findings reveal that e-Court has had a positive impact on accelerating case administration, reducing litigation costs, and improving transparency in civil procedures. Services such as e-Filing, e-Payment, and e-Summons have significantly shortened the time and expenses compared to conventional procedures. Nevertheless, the study also identifies several challenges, including limited technological infrastructure in certain regions, low digital literacy among both society and court officials, as well as inconsistent judicial understanding regarding the evidentiary strength of electronic documents. These conditions indicate that the efficiency of e-Court remains partial and not yet fully inclusive. Theoretically, this research reinforces the relevance of the law and economics efficiency theory (Posner) in assessing procedural effectiveness, while also highlighting the challenges of access to justice (Cappelletti & Garth) in the context of judicial digitalization. In practical terms, the study implies the need for strengthening digital evidence regulations, enhancing human resource capacity, and expanding equitable infrastructure development so that e-Court can truly embody the principles of simple, fast, and low-cost justice. Further research is recommended to explore quantitative empirical data in order to deepen comparative analysis before and after the implementation of e-Court.